Trinidad, Victoria Institute - Power (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows the Victoria Institute which built to commemorate the Golden Jubilee of Queen Victoria’s reign. Fire gutted the building in 1920s and it was rebuilt in 1923, but renamed the National Museum and Art Gallery in 1965. The original building was designed by Daniel Mienerts Hahn, a German who worked in the Dept of Public Works, Trinidad. Postcard No. 13.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historic buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; National museums--Trinidad and Tobago; Museums--Trinidad and Tobago; Architecture--Trinidad and Tobago; Streets--Trinidad and Tobago; Frederick Street (Port of Spain)